Evaluation and poverty reduction : proceedings from a World Bank conference - Feinstein, Osvaldo (World Bank WashingtonUS, 2000)
Looks at topics such as the role of targeted and pro-poor growth policies and programs for poverty reduction; the design of social funds; safety nets; crisis provention, and social service delivery mechanisms; and ways to include civil society and private sector institutions more effectively in development. Discusses evaluation methodologies such as measuring development impact, with special emphasis on factoring in externalities, choosing appropriate counterfactuals, and including randomization in evaluation design. Discusses also mechanisms, benefits and costs of participatory evaluation.